Respostas funcionais ao ambiente não são explicados por filogenia em aves e mamíferos no continente americano - Werneck, Rhayane Pires (2019)
Over the years, ecologists have tried to understand the diversity of attributes in communities and how this reflects how species respond to the environmental gradient. It is known that different environmental conditions such as temperature, precipitation and productivity are able to select attributes and result in different configurations of functional diversity patterns. These gradient responses may or may not be structured in phylogeny, which argues that phylogenetically closest lines will respond in a similar manner. Moreover, given the different histories and evolutionary origins, lineages (e.g. families) may respond differently when compared to whole groups (e.g. orders). Thus, we aimed to understand if climatic variables and productivity gradient are able to explain the diversity of attributes of groups and families of birds and mammals in the American continent. In addition, we wanted to understand if these responses to environmental gradients had a phylogenetic signal. For this, we calculated the functional diversity for the group and bird and mammal and their families in Protected Areas of the American continent, and performed a multiple regression analysis between the values of diversity and variables of temperature, precipitation, seasonality and productivity gradient (for the classes and their respective families). Afterwards, we performed a variation partitioning analysis to understand the contribution of each variable to the values of functional diversity. We then performed a phylogenetic signal analysis on the slope values (beta) resulted from multiple regression analyzes. We found that productivity explained most of the values of functional diversity for the families of birds and mammals. In addition, the responses to the environmental gradient were quite different for the families when compared to the group as a whole. We also did not find a phylogenetic signal in the response of bird and mammal’s families. These results lead us to conclude that studying whole groups rather than finer taxonomic scales can mask different responses to ecological and evolutionary factors of community structuring, once lineages have different evolutionary histories and respond differently to environmental factors. Furthermore, our results show that lineages with similar environmental gradient responses are not necessarily related (evolutionary convergence) and, therefore, there is no evidence for niche conservation.